Peer assessment to promote self-regulated learning with technology in higher education: systematic review for improving course design - Ortega-Ruipérez, Beatriz; Correa-Gorospe, José Miguel (Frontiers in Education, 2024)
Peer assessment is one of the approaches to develop self-regulation of learning. When evaluating the work of peers, metacognitive strategies of critical reflection are employed. They improve their own learning especially if evaluative feedback and/or suggestions for modification are provided. The aim of this systematic review is to learn how technology can facilitate self-regulation of learning, using peer assessment activities. We focus on higher education. To achieve the objective, we searched WoS and Scopus, obtaining 15 publications that concatenate the four search terms: self-regulated learning, peer assessment, higher education, and technology. These four terms must appear in the title, abstract or keywords. In this way, we ensure that the topic to be reviewed is central to the publication. The results are analysed using the model for systematic review, which has three phases: description, synthesis, and critique. A proposal has been made to improve the design of courses in virtual classrooms, focusing on Moodle, and to include peer evaluation to improve self-regulated learning. It highlights the possibility of virtual classrooms to configure a rubric to guide the evaluation, together with the request for mandatory comments to justify the evaluation. This helps the student reflect on what is wrong and why, and how to improve. It also highlights the facility to randomly assign a specific number of tasks per reviewer or per task, and to make the whole process completely anonymous. The technology allows short deadlines for submission and review times to be maintained for instant feedback, as it can be configured with a single click. Finally, and related to this, Moodle can reopen the submission phase, to send an improved version based on feedback, and the evaluation phase, to check that the proposed improvements have been made. This helps to a greater extent to apply metacognitive strategies.